2019
DOI: 10.1093/eurpub/ckz186.192
|View full text |Cite
|
Sign up to set email alerts
|

School bullying among Tunisian adolescents: prevalence and psychosocial outcomes

Abstract: Background Bullying is a serious public health concern affecting the emotional well-being of pupils. We conducted this study to examine the prevalence of bullying, its psychosocial associated factors and the perceived involvement of parents, teachers, and classmates to counteract this behavior. Methods This is a cross-sectional study conducted in 2015 among a representative sample of pupils enrolled in 14 colleges in Sousse u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
0
9
1
Order By: Relevance
“…A meta-analysis by Modecki et al, encompassing 80 studies that investigated bullying involvement rates of students (aged between 12 and 18 years), revealed wide variation in prevalence rates across contexts, with mean prevalence rates of 36% for victimization [ 17 ]. Even though there is still significant under-representation of developing countries of the Arab world in the research literature related to school bullying, similar variations in estimates have been documented, with prevalence rates of 7% in Jordan [ 18 ], 11.7% in Tunisia [ 19 ], 16% the United Arab Emirates [ 20 ], 9.9–20.6% in Algeria [ 21 ], and 49.1% in Lebanon [ 22 ]. Thus, Lebanon seems to have one of the highest prevalence rates of bullying in the Arab region and even worldwide, with almost 1 in 4 Lebanese adolescents having been estimated to be involved in bullying [ 23 ].…”
Section: Introductionmentioning
confidence: 89%
“…A meta-analysis by Modecki et al, encompassing 80 studies that investigated bullying involvement rates of students (aged between 12 and 18 years), revealed wide variation in prevalence rates across contexts, with mean prevalence rates of 36% for victimization [ 17 ]. Even though there is still significant under-representation of developing countries of the Arab world in the research literature related to school bullying, similar variations in estimates have been documented, with prevalence rates of 7% in Jordan [ 18 ], 11.7% in Tunisia [ 19 ], 16% the United Arab Emirates [ 20 ], 9.9–20.6% in Algeria [ 21 ], and 49.1% in Lebanon [ 22 ]. Thus, Lebanon seems to have one of the highest prevalence rates of bullying in the Arab region and even worldwide, with almost 1 in 4 Lebanese adolescents having been estimated to be involved in bullying [ 23 ].…”
Section: Introductionmentioning
confidence: 89%
“…A cluster sampling method was used to select a random sample and the sample size was calculated according to the following formula: n = Z α/2 2 × (p × q) / i 2 (n = minimum sample size, Z α/2 = 1.96 (α = 0.05), p = 0.12; q = 0.88, i = 0.03). At a 95% confidence interval and assuming a problem frequency of 12% [ 9 ] and a 5% margin of error, the minimal sample size required was 451 school students. A design effect of 2 was used to compensate for the error of the estimate encountered using cluster sampling (instead of simple random sampling) and 20% was added to compensate for potential non-response.…”
Section: Methodsmentioning
confidence: 99%
“…The Arabic version of the revised and self-reported Olweus Bully/Victim Questionnaire (BVQ) was used to assess bullying victimization [ 9 , 19 ]. Only items on victimization were considered for this study (18 items).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Tunisia, few studies have been conducted to assess the prevalence of cyberbullying among adolescents. A study by Bassem Abida in 2019 (4) at Sfax, Tunisia revealed a rate of 34.4%, and another study in 2018 (5) in Sousse found a prevalence of 22.2% among 1111 middle school students. This urgency is further underscored by a study involving samples of adolescents from both Tunisia and Lebanon, which has highlighted a signi cant connection between cyberbullying and mental distress.…”
Section: Introductionmentioning
confidence: 98%